Challenges of virtual team leadership: Cisco systems case - Reynaud, Darya de Miranda (2014)
In recent decades, a powerful trend has emerged in teams across organizational boundaries, as well as a dramatic change to the face-to-face aspects of common work relationships. The Internet and a quick development in electronic technologies have created an unprecedented ability to work together from a distance. In the conditions of every time more tough competition internationally, Cisco Systems, a multinational company of the US origin, acting in the area of networking equipment, is constantly striving to excel its performance via improving the technology, processes and investing into its human capital. Being one of the market leaders in the development of hardware and software enabling distant, or virtual, team work - Cisco itself has been largely using a model of virtual networks and virtual teams in various business units. In this thesis, the author explores the concept of a virtual team and conducts a study of sixteen virtual teams at Cisco Systems to evaluate the state of their current functioning, identify strengths and challenges, revise the existing managerial solutions and suggest improvements. As a result of the research, the author proposes a model of successful virtual team tailored for the environment of Cisco Systems accompanied with a series of recommendations, which could also be useful for other multinational companies.